EMPLOYABILITY THROUGH TRANSITION PROGRAM FOR STUDENTS WITH SPECIAL NEEDS (Proceedings of International Conference on Special Education, 2015)
Employability is an additional criterion comprises three main aspects comprises of academic skills, thinking and personality qualities that are valued by employers during the recruitment process. Through the implementation of the transition program for students with special educational needs (SEN), employability skills were applied as a complement to the basic skills of the chosen career. Exposure to career paths are important to enable students with special educational needs to be more independent and confident to face the real working life and able to compete to get a job after completing school. This field study was carried out for seven weeks in a shopping mall, Hypermarket in Selangor to see the progress of an individual student, in term of social, behaviour, self-respect, and the ability to meet and comply with all criteria; basic academic skills, higher-order thinking skills and personal qualities’ and analysis tasks in the workplace. Observation and feedback of teachers and parents were analyzed. The student’s progress recorded and analysed during the ongoing transition program. The participant of this study was a 16 years old student diagnosed with Attention Deficit Hyperactivity Disorder (ADHD). The finding shows that there are positive changes recorded in all aspects. Implication of this study are related to the provision of a wider range of employability skills and attract employers to cooperate in providing guidance and training to students with special needs.